2013
DOI: 10.1007/s11633-013-0716-y
|View full text |Cite
|
Sign up to set email alerts
|

An Optimization Algorithm Employing Multiple Metamodels and Optimizers

Abstract: Modern engineering design optimization often relies on computer simulations to evaluate candidate designs, a setup which results in expensive black-box optimization problems. Such problems introduce unique challenges, which has motivated the application of metamodel-assisted computational intelligence algorithms to solve them. Such algorithms combine a computational intelligence optimizer which employs a population of candidate solutions, with a metamodel which is a computationally cheaper approximation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Here all the components of z * are taken as 1 000. The desired humidity profiles U * corresponding to z * can be obtained using (16). The nodal humidity profiles can be obtained from z(t).…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here all the components of z * are taken as 1 000. The desired humidity profiles U * corresponding to z * can be obtained using (16). The nodal humidity profiles can be obtained from z(t).…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…The approach involved discretization of governing equations with FE method and obtaining a reduced nonlinear dynamic system of much smaller size with almost same dynamic property as the original using POD method. A controller based on optimal control theory [16] is designed for the reduced model so that the output reaches to a desired profile. It has also been shown that the controller acts fairly good for the original model as well.…”
Section: Introductionmentioning
confidence: 99%
“…This measure is then used to select the most suitable surrogate model. Tenne [27] proposes a framework in which the algorithm to construct surrogate models as well as the search algorithm is adapted online during the run.…”
Section: A Evolutionary Optimization Using Surrogate Modelsmentioning
confidence: 99%
“…Common metamodel variants include artificial neural networks, Kriging, polynomials, and radial basis functions (RBFs) (Wortmann et al, 2015;Forrester and Keane, 2008;Queipo et al, 2005;Regis, 2014;Viana et al, 2013;Tenne, 2013). Metamodel-assisted frameworks typically operate by first training a metamodel and then seeking its optimum.…”
Section: 1mentioning
confidence: 99%